An evaluation of the Aerie Real campaign: Potential for promoting positive body image?. (May 2019) - Convertino, Alexandra D; Rodgers, Rachel F; Franko, Debra L; Jodoin, Adriana
This study evaluated the impact on young women's body satisfaction of an advertising campaign: Aerie Real, which included images of models who were not digitally modified. In total, 200 female students were randomly allocated to view either Aerie Real images or digitally modified images from previous campaigns. In the total sample, no condition differences appeared. However, participants with high appearance comparison reported a smaller decrease in body satisfaction after viewing the Aerie Real images as compared to those viewing previous images ( p = .003). Findings provide preliminary support for the Aerie Real campaign as less deleterious form of media for body image.